Constructive friction? Charting the relation between educational research and the Scholarship of Teaching and Learning - Larsson, Maria; Mårtensson , Katarina; Price, Linda; Roxå, Torgny (Teaching and Learning Inquiry, 2020)
While educational research and the Scholarship of Teaching and Learning (SoTL) are overlapping fields, over time there has appeared considerable friction between the two. There are claims that educational research has been tainted by SoTL’s emergence and that those engaged in SoTL lack adequate training. They maintain that those engaged in SoTL would benefit from a better understanding of educational research theories and methods. Some engaged in SoTL perceive educational research as too distanced from practice. What underpins these perceived differences between the two fields? How might this friction be explained? The study described in this article explored empirical, interview-based viewpoints from new and experienced educational researchers and SoTL scholars, respectively. Participants were purposefully drawn from attendees at two European conferences specializing in educational research and SoTL. The data was examined using thematic analysis and focused mainly on the perceived differences between these communities. The central themes that emerged where differences occurred are community membership and governance, scope and purpose of inquiry, and intended recipients of inquiry results. Some differences include what and who determines the value of the contribution to the field and why it is valuable. This article provides an empirically based understanding of the relative attributes of both communities. We hope that it leads to future discussions about further developing fruitful and constructive interrelationships.